Power to the fiscal? - Aslan, Cigdem,Irwin, Timothy C. (World Bank Group, Macroeconomics, Trade and Investment Global Practice, 2020)
Ministries of finance are often asked to guarantee a state-owned electricity utility's payments to an independent power producer under a power-purchase agreement. To decide whether to grant the guarantee, the ministry should have at least a rough estimate of the guarantee's expected cost. Making use of an analogy between a power-purchase agreement and a debt contract, this paper shows how the ministry can get such an estimate by applying a method developed to estimate the expected cost of debt guarantees. An estimate of the probability of the utility's not being able to meet its obligations under the power-purchase agreement can be derived from the utility's actual or estimated credit rating in the absence of government support. The government's expected payments under the guarantee can then be estimated by multiplying the utility's payments under the power-purchase agreement by this probability. The estimates produced by the method will be imprecise, but the method may be easier to apply than alternative methods, and an imprecise estimate may be better for policy makers than no estimate
10.1596/1813-9450-9271
Keywords: Graue Literatur; guarantee; power-purchase agreement; independent power producer; electricity; fiscal risk